Industrial robotics in the lean enterprise : a case study in semi-conductor company - Safady, Hammam M. H. (2017)
Industrial robotics replaced human workers in almost all field due to their abilities in multitasking, flexibility and configurability in any position they are involved in. However, implementing industrial robotics is challenging due to their high cost, expert handling and complexity. The case study determined the industrial robotics as a desirable tool in lean enterprise and through studying these areas availability, ease of use, standardization and visualization it shows the current mapping of the industrial robotics. Performance measurement of the industrial robotics is determined using the QCDAC method or (quality, cost, delivery, accountability and continual improvement). In terms of performance identification and ranking interpretive structural modelling (ISM) methodology is used to identify the most affected variable of the model. Cross tabulation showed the intersection result between the usage of industrial robotics and their performance to clarify the industrial robotics performance in these areas in which the industrial robotics was fit with and compatible with lean enterprise. The results showed that introducing the industrial robotics into lean enterprise will support it in terms of quality improvement, cost reduction and efficiency which lead the company to become a world class manufacturer.